Implementation of national policies and interventions ( WHO Best Buys ) for non-communicable disease prevention and control in Ghana: a mixed methods analysis - Baatiema, L; Sanuade, OA; Kretchy, IA; Okoibhole, L; Kushitor, SB; Haghparast-Bidgoli, H; Awuah, RB; Amon, S; Mensah, SK; Grijalva-Eternod, CS; Adjaye-Gbewonyo, K; Antwi, P; et al. (BioMed Central, 2024)
Background: The World Health Organization (WHO) encourages all member states to adopt and implement a package of essential evidence-based interventions called the Best Buys to reduce the burden of non-communicable diseases (NCDs). To date, little is known about the implementation of national policies and interventions for NCD control in the WHO member states in sub-Saharan Africa. Our study aimed to evaluate the implementation of national policies and interventions (WHO Best Buys) for non-communicable disease prevention and control in Ghana. Methods: This was explanatory mixed methods research which started with a document review of Ghana’s WHO Best Buys scores from the 2015, 2017, 2018, 2020 and 2022 WHO NCD Progress Monitor Reports. Thereafter, we conducted 25 key informant interviews and one focus group discussion (11 participants) with key policymakers and stakeholders in the NCD landscape in Ghana to understand the implementation of the NCD policies and interventions, and the policy implementation gaps and challenges faced. Data from the NCD Progress reports were presented using mean scores whilst the qualitative data was analysed thematically. Results: Ghana has shown some advancements in the implementation of the WHO Best Buys measures. Ghana’s implementation scores for 2015, 2017, 2020 and 2022 were 5.0, 9.0, 5.0 and 5.5 respectively, against the mean implementation scores of 7.6/19 for lower-middle-income countries and 9.5/19 for upper-middle-income countries. Efforts to decrease major risk factors such as excessive alcohol consumption and unhealthy diet have been progressing slowly. The most common challenges were related to a) the role of socio-cultural factors, b) stakeholder engagement, c) enforcement and implementation of public health policies, d) implementation guidelines, e) public awareness and education on NCDs, f) financing of NCD prevention and control, g) curative-centered health systems, and h) over-centralization of NCD care. Conclusion: Ghana has made progress in adopting the WHO Best Buys targeting risk factors of NCDs. However, the country faces contextual barriers to effective implementation. With the retrogression of some measures over time despite making progress in some earlier years, further investigation is needed to identify facilitators for sustained implementation of the WHO Best Buys interventions.